The Influence of Student Knowledge and Awareness Sharia Insurance on Interest To Buy Insurance Sharia Personal Accident - Sahri Aramiko; Zuhrinal Zuhrinal; Nursantri Yanti (Asosiasi Dosen Akuntansi Indonesia, 2021)
Sharia personal accident insurance is protection against all risks of a person resulting in death and accidents to that person. In their daily activities, students face many risks, such as traveling from home to campus that experiences a disaster or unwanted events that result in serious injuries and hinder students in their activities. The purpose of this study is to find out whether knowledge and awareness have a significant and simultaneous effect on the interest of Sharia Insurance students at FEBI UIN SU to buy sharia personal accident insurance products. This study uses a quantitative approach by conducting t-test and F-test. This study uses multiple regression analysis. The variables used in this study are knowledge and awareness and buying interest to buy Sharia personal accident insurance. The results of this study indicate that the knowledge coefficient has a partial effect on buying interest in sharia personal accident insurance products. The coefficient of awareness partially affects the interest in buying sharia personal accident product. There is a significant influence of knowledge and awareness on interest in buying sharia personal accident insurance products.